National Character and State Defense Based on Local Tapis Lampung Culture as an Effort to Strengthen National Identity - Ramadhoni, M. Bram Efano; Siahaan, Timbul; Jandhana, I B Putra (CV. Rayyan Dwi Bharata, 2024)
Indonesia, with a diverse population of many ethnic groups and rich cultural heritage, is a global, non-competitive multicultural country. Like the variety of flowers in this country's gardens, Indonesia's mosaic of cultures and beliefs is also diverse. Indonesia's rich cultural diversity attracts tourists and is a source of innovation for creative industries. In an effort to fortify Indonesian nationalism, this research aims to display handmade art works by Tapis Lampung. The research methodology used is qualitative using descriptive literature study methodology. Based on research findings, Tapis Lampung is a type of traditional textile that is embroidered with decorative sugi designs using cotton thread and silver or gold thread. The Lampung indigenous people store their life values and character in this Tapis cloth, which is also used in various traditional, religious and wedding events. One of the characteristics of Indonesian society is the Tapis Lampung cloth which is widely sold both domestically and internationally. Tapis Lampung is a cultural achievement of the Lampung people, according to examination from various sources.